Has The Covid-19 Pandemic Changed Demand for Online Gig Work? - Izabela OSTOJ (Communications of International Proceedings, 2021)
The development of online gig work is determined by the demand for this type of services - by its size and structure. This stems from the permanent surplus of the supply of these services compared to the demand for them in the global online gig economy. The study aims to identify the changes in the demand for online gig economy services during the Covid-19 pandemic in relation to previously observed patterns. On the one hand, the pandemic has caused a decrease in economic activity, on the other hand, it has raised an interest in services provided online, which has contributed to the increased demand for services coordinated through global online platforms. This has led to the growth of this market and triggered certain changes in the patterns previously established, although the core characteristics developed in recent years have remained unchanged.
Keywords: Online Gig Work; Gig Economy; Covid-19; Online Labour Index.